2021
DOI: 10.3390/su13116473
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Religiosity and Food Consumption Culture on Food Waste Intention in Saudi Arabia

Abstract: The Kingdom of Saudi Arabia (KSA) is among the top food-wasting countries worldwide, despite it being considered a religious society. Hence, an important question has emerged “to what extent and by what mechanism can religiosity influence food waste intention?”. This research answers this research question and examines the direct impact of both religiosity and food consumption culture on food waste intention as well as the indirect impact through the constructs of theory of planned behavior. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 63 publications
5
72
0
Order By: Relevance
“…The results of benchmark regression based on Equation ( 2) are shown in Table 3. It indicates that religious beliefs significantly negatively affect the food waste rate of Chinese rural households if other variables remain the same, in line with the conjecture of Abdelradi [10] and the finding in Saudi Arabia [42] as well as in Poland [31]. This means that the negative association between religion and food waste is not only established in religious societies.…”
Section: Benchmark Regressionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results of benchmark regression based on Equation ( 2) are shown in Table 3. It indicates that religious beliefs significantly negatively affect the food waste rate of Chinese rural households if other variables remain the same, in line with the conjecture of Abdelradi [10] and the finding in Saudi Arabia [42] as well as in Poland [31]. This means that the negative association between religion and food waste is not only established in religious societies.…”
Section: Benchmark Regressionsupporting
confidence: 79%
“…For example, an interview with 60 rural families in rural Lebanon discovered that religiosity encourages food waste avoidance [41]. A study in Saudi Arabia also suggested that religious beliefs may influence individual food wastage intention [42]. A similar study from India also confirmed that various religions could reduce individual food waste intention to varying degrees [33].…”
Section: Introductionmentioning
confidence: 97%
“…The TPB was adopted extensively to predict customer intention and behaviour in different contexts beyond the hospitality and tourism contexts. With regard to the hospitality context, the theory was adopted to predict food consumption decisions [ 17 ], intention to purchase local food products [ 18 ], customer intention and behaviour towards food waste [ 19 ], intention and behaviour towards menus with organic information in restaurants [ 20 ], attitude towards and intention to buy organic food [ 9 ], intentions to select eco-friendly restaurants [ 48 ] and purchasing intentions of genetically modified foods based on their nutrition labelling [ 49 ]. Recent research [ 46 ] suggested that attitudes, descriptive norms and nutrition literacy are significant predictors of food label use intentions.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The TPB framework has been applied extensively [(see for example 17–20)] to predict human intention and behaviour. For example, the theory was adopted to predict food consumption decisions [ 17 ], intentions to purchase local food products [ 18 ] and customer intention and behaviour towards food waste [ 19 ]. Shin et al, [ 20 ] adopted the TPB to explore and examine customer intention and behaviour towards organic menus in restaurants and gained a better understanding of the determinants of customer intention and behaviours regarding organic menu.…”
Section: Introductionmentioning
confidence: 99%
“…Stancu et al [11] stated that food waste disposal behavior is complexly affected by individual routines, psychological factors, and social environment. According to Elshaer et al [12], a country's culture and religion have a great influence on the food waste problem, and, in particular, the food consumption culture has a significant influence on food waste disposal behavior. Fortunately, Rodgers et al [13] stressed that amid the global pandemic situation, many people invested significant time in cooking and reduced their grocery shopping excursions as they spent more time at home than before the pandemic.…”
Section: Introductionmentioning
confidence: 99%